TPOR: an integrated socio-ecological framework to inform management toward resilience - Manley, Patricia N.; Povak, Nicholas A.; Wilson, Kristen N. (Frontiers in Environmental Science, 2025)
Socio-ecological resilience recognizes that humans and nature are inextricably connected, and humans play an increasingly central and active role in determining the fate of ecosystem resilience. For decades, managers and scientists have sought effective approaches for managing forest composition, structure, and processes to improve resilience properties. Management actions that encompass large landscapes tend to engage a broad spectrum of stakeholders and perspectives about resilience. Translating resilience concepts into concrete and measurable objectives and outcomes and effectively communicating landscape management strategies presents many practical and conceptual challenges. Climate change is increasing the burden faced by managers to increase the pace and scale of management actions in an attempt to enhance the resilience of forested landscapes to more extreme environmental conditions. Through a process that engaged a diversity of stakeholders, we developed a framework for socio-ecological resilience intended to support, quantify and expedite a range of landscape resilience management activities. The Ten Pillars of Resilience (TPOR) Framework is an operational method to organize, evaluate, inform, guide, monitor, and document socio-ecological conditions across landscapes. The Framework’s information hierarchy consists of three levels: 1) Pillars, which represent the primary constituents of resilient socio-ecological systems across landscapes; 2) Elements, which reflect the core features of each Pillar; and 3) Metrics, which represent the characteristics of each Element that directly or indirectly have bearing on resilient outcomes. The TPOR Framework has been used to support large-scale restoration policies, planning, assessments, and accomplishments. We discuss how the Framework can serve as a construct for integrating past, current, and future conditions as a function of management, climate, and other disturbances. It has demonstrated value in supporting the needed pace, scale, and effectiveness of management investments by providing a consistent and scientifically robust foundation for quantitatively representing the spectrum of facets of resilience in socio-ecological systems in balancing near-term gains and long-term resilience objectives.